Current development state of Vietnamese service sector - Nguyen, Hong Son (2016)
Service sector has proved to be an important source of economic growth and social development of Vietnam over the past two decades. However, it is also subjected to numerous criticisms for a lack of facilities, monopoly, insufficient qualified service workers, poor quality, corruption, non-transparency, favoritism, and discrimination. At present, liberalization is expected to bring about significant changes to the Vietnamese services in terms of number of service providers, service structure, supply mode, governance, and regulations as well as service price and quality. This article will describe the current state of development of the Vietnamese service sector and identify the service gaps that need to be bridged in the coming years as Vietnam will implement the new socio-economic development strategy from now to the year 2020.